Quilting for hire : start your own longarm or custom quiltmaking business : vision, business plan, tools & supplies, branding, marketing & more - Pagliai, Shelly, 1962- (C&T Publishing, 2022)
"An interactive handbook for starting or expanding a professional longarm or custom quiltmaking business, with detailed guidance on writing a business plan, setting up a studio, working with customers, dealing with accounting and taxes, marketing a business, creating forms and contracts, and managing everyday logistics of insurance, supplies, and shipping"-- Provided by publisher"--